METHODS OF FORMING AND DEVELOPING SKILLS RELATED TO TECHNICAL MECHANICS IN ENGINEERING STUDENTS - Suyunova Yulduz (American Journals Publishing, 2025)
Modeling is important at the current stage of educational development. As a result of the radical change of educational paradigms, new requirements for modeling innovative pedagogical systems appear.